Trends in operation rates for inguinal hernia over five decades in England: database study. - Maisonneuve, J; Yeates, D; Goldacre, M (Springer Paris, 2015)
PURPOSE: We aimed to study trends over time in operation rates for inguinal hernia with and without obstruction over five decades. METHODS: Routine hospital statistics were used to analyse trends in National Health Service hospitals in England (1968-2011). RESULTS: All-England admission rates for elective repair of unobstructed inguinal hernia in males were 240.8 episodes per 100,000 population [95 % confidence interval (CI) 234.5-247.2] in 1968 and were relatively stable until 2003 after which they declined to 217.1 (215.4-218.8) by 2011. However, the stability of the all ages rates masked a large decline in admission rates in the young (e.g. 425 per 100,000 in 1968-1970 in males under 1 year of age, down to 155 per 100,000 in 2007-2011) and a large increase in the elderly (e.g. 247 in 1968-1970 per 100,000 males aged 75-84, up to 799 per 100,000 in 2007-2011). All-England admission rates for obstructed inguinal hernia in males almost halved, from 19.3 episodes (17.4-21.2) in 1968 to 10.7 episodes (10.3-11.0) per 100,000 population in 2011. Admission rates for females gradually declined over time for both unobstructed and obstructed inguinal hernia. CONCLUSION: Hospital admission rates for elective operation on inguinal hernia without obstruction, for all ages combined, have been relatively stable over five decades, but this masked big differences between age groups. Rates of obstructed hernia have declined over time, particularly in the early years covered by the study, and have not shown an increase associated with the recent fall in elective surgery for hernia repair.